1984
DOI: 10.1002/1097-0142(19840901)54:5<794::aid-cncr2820540503>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Intracarotid infusion of cis-diamminedichloroplatinum in the treatment of recurrent malignant brain tumors

Abstract: Thirty‐five patients with malignant brain tumors (23 with primary brain tumors and 12 with brain metastases) progressing after cranial irradiation chemotherapy received cisplatin, 60 to 120 mg/m2, into the internal carotid artery by a transfemoral approach. Courses of therapy were repeated every 4 weeks. Therapeutic evaluation was performed monthly using the CT scan of the brain and clinical neurologic examination. Thirty patients were evaluable for response. Of 20 evaluable patients with primary malignant bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(30 citation statements)
references
References 11 publications
3
26
0
1
Order By: Relevance
“…Data from several studies showed that at least 60 mg/m 2 of IA DDP was adequate to achieve a response [14][15][16]. All but one of our patients received 75-100 mg/m 2 of DDP per dose.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Data from several studies showed that at least 60 mg/m 2 of IA DDP was adequate to achieve a response [14][15][16]. All but one of our patients received 75-100 mg/m 2 of DDP per dose.…”
Section: Discussionmentioning
confidence: 77%
“…Her partial response may have been from this fraction of tumor. The efficacy of IA DDP was less than that seen in most other trials of IV [12,13] or IA [14][15][16][17][18] administered DDP. Our response rate was also considerably less than those obtained with IV BCNU [3,4].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Intraarterial infusions of cisplatin have been occasionally useful in patients with recurrent malignant gliomas, including patients previously treated with nitrosoureas [3]. Unfortunately, intraarterial cisplatin may induce severe neurological and ophthalmological complications [3]. Intravenous cisplatin has been successful in various neoplasms including CNS malignancies [4] but the administration of this drug was associated with a variety of toxicites.…”
mentioning
confidence: 91%
“…Aida and Bodell [2] did not find cross resistance between chlornitrosoureas and cisplatinum on human malignant gliomas cell lines. Intraarterial infusions of cisplatin have been occasionally useful in patients with recurrent malignant gliomas, including patients previously treated with nitrosoureas [3]. Unfortunately, intraarterial cisplatin may induce severe neurological and ophthalmological complications [3].…”
mentioning
confidence: 99%